Electroacupuncture Mitigates Hippocampal Cognitive Impairments by Reducing BACE1 Deposition and Activating PKA in APP/PS1 Double Transgenic Mice. (15th May 2019) - Tang, Yinshan; Shao, Shujun; Guo, Yu; Zhou, You; Cao, Jin; Xu, Anping; Wu, Jihong; Li, Zhigang; Xiang, Dulian
Abstract : Increased amyloid- β (A β ) plaque deposition is thought to be the main cause of Alzheimer's disease (AD). β -Site amyloid precursor protein cleaving enzyme 1 (BACE1) is the key protein involved in A β peptide generation. Excessive expression of BACE1 might cause overproduction of neurotoxins in the central nervous system. Previous studies indicated that BACE1 initially cleaves the amyloid precursor protein (APP) and may subsequently interfere with physiological functions of proteins such as PKA, which is recognized to be closely associated with long-term potentiation (LTP) level and can effectively ameliorate cognitive impairments. Therefore, revealing the underlying mechanism of BACE1 in the pathogenesis of AD might have a significant impact on the future development of therapeutic agents targeting dementia. This study examined the effects of electroacupuncture (EA) stimulation on BACE1, APP, and p-PKA protein levels in hippocampal tissue samples. Memory and learning abilities were assessed using the Morris water maze test after EA intervention. Immunofluorescence, immunohistochemistry, and western blot were employed to assess the distribution patterns and expression levels of BACE1, APP, and p-PKA, respectively. The results showed the downregulation of BACE1 and APP and the activation of PKA by EA. In summary, EA treatment might reduce BACE1 deposition in APP/PS1 transgenic mice and regulate PKA and its associated substrates, such as LTP to change memory and learning abilities.